Interlocutor differential effects on the expressive language skills of Spanish-speaking English learners. (3rd March 2016) - Rojas, Raúl; Iglesias, Aquiles; Bunta, Ferenc; Goldstein, Brian; Goldenberg, Claude; Reese, Leslie
Abstract: Purpose : The primary objective of this study was to investigate the relationship between language use with different interlocutors, maternal education level and the expressive language skills of US English learners (ELs) in Spanish and English. Method : Two hundred and twenty-four Spanish-speaking ELs in kindergarten provided narrative language samples in Spanish and English. Parents completed a questionnaire of maternal education level and language use with parents, older siblings and peers. Result : Multiple linear regression analyses demonstrated that language used with different interlocutors and maternal education level had unique effects on participants' expressive language skills. ELs' expressive language skills in English were predicted by interactions with older siblings, peers and maternal education level; Spanish expressive language skills were predicted by interactions with older siblings. Conclusion : The findings from this study suggest that the determination of language experience of school-age bilingual children should examine differential language use with multiple interlocutors, particularly interactions with older siblings and peers.